2002
DOI: 10.1161/01.cir.0000036743.07406.53
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Tolerance

Abstract: T he first part of this review provided a synopsis of the recent literature about superoxide anion (·O 2 Ϫ ) production, endothelial dysfunction, and the neurohormonal activation that follow long-term administration of organic nitrates. In this issue of Circulation, we will try to integrate these observations with other separate, and, to a certain extent, antagonistic hypotheses that have been proposed for the development of nitrate tolerance. [1][2][3] Hypotheses concerning the pathogenesis of tolerance have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(42 citation statements)
references
References 63 publications
3
36
1
Order By: Relevance
“…This was demonstrated by significant reductions in percentage shortening and maximal rates of shortening and relaxation of the rabbit cardiac myocytes. Similar effects on the heart have been demonstrated previously [10,13,14]. Inhibition of the cyclic GMP protein kinase with KT5823 partially reversed these effects.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This was demonstrated by significant reductions in percentage shortening and maximal rates of shortening and relaxation of the rabbit cardiac myocytes. Similar effects on the heart have been demonstrated previously [10,13,14]. Inhibition of the cyclic GMP protein kinase with KT5823 partially reversed these effects.…”
Section: Discussionsupporting
confidence: 83%
“…Long-term administration of nitrates causes nitrate tolerance or tachyphylaxis in many species including man [4,5,7,8,10,11]. Recently, there has been a strong focus on a proposed free radical hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, GTN tolerance (Fadel et al, 2012) and corresponding biological and chemical changes (Gori and Parker, 2002;Daiber et al, 2009) have been attributed to ROS-induced oxidative stress. In this study, we observed that more ROS were produced under GTN tolerance conditions.…”
Section: Discussionmentioning
confidence: 99%
“…[33,35] Despite of the extensive usage the past, the effectiveness of organic nitrates and nitrites are limited for prolonged continuous treatment due to the development of pharmacologic tolerance and endothelial dysfunction. [36] This is because the NO donors rely on enzymatic activation to release NO, particularly for inflammatory conditions. In addition, in vivo studies have shown that endothelial dysfunction and oxidative stress probably aggravate the tolerance, and increase the risk in cardiovascular events.…”
Section: Biomaterials For 3d Cell Biology Prospective Articlementioning
confidence: 99%